Generic recircumscriptions of Oncidiinae (Orchidaceae: Cymbidieae) based on maximum likelihood analysis of combined DNA datasets - Neubig, Kurt M. (2012)
Phylogenetic relationships within the orchid subtribe Oncidiinae sensu Chase were inferred using maximum likelihood analyses of single and multilocus DNA sequence data sets. Analyses included both nuclear ribosomal internal transcribed spacer DNA and plastid regions (matK exon, trnH-psbA intergenic spacer and two portions of ycf1 exon) for 736 individuals representing approximately 590 species plus seven outgroup taxa. Based on the well resolved and highly supported results, we recognize 61 genera in Oncidiinae. Mimicry of oil-secreting Malpighiaceae and other floral syndromes evolved in parallel across the subtribe, and many clades exhibit extensive variation in pollination-related traits. Because previous classifications heavily emphasized these floral features, many genera recognized were not monophyletic. Our classification based on monophyly will facilitate focused monographs and clarifies the evolution of morphological and biochemical traits of interest within this highly diverse subtribe.